Evaluation of a diverse population of morphed human body models for prediction of vehicle occupant crash kinematics. Issue 10 (27th July 2022) - Larsson, Karl-Johan; Pipkorn, Bengt; Iraeus, Johan; Forman, Jason; Hu, Jingwen
Abstract: Morphing can be used to alter human body models (HBMs) to represent a diverse population of occupants in car crashes. The mid-sized male SAFER HBM v9 was parametrically morphed to match 22 Post Mortem Human Subjects, loaded in different configurations. Kinetics and kinematics were compared for the morphed and baseline HBMs. In frontal impacts, the morphed HBMs correlated closer with the kinematics of obese subjects, but lower to small females. In lateral impacts HBM responses were too stiff. This study outlines a necessary evaluation of all HBMs that should be morphed to represent the diverse population in vehicle safety evaluations.